A Lady's Life in the Rocky Mountains - Bird, Isabella L. (Cambridge library collection. North American History, 1879)
After the success of The Englishwoman in America (also reissued in this series), the indefatigable Isabella Bird (1831–1904) continued her travels – first to Scotland, then to Australia and Hawaii – before returning to the United States and taking up residence in what was then the newest state, Colorado. Her adventures here – recorded as letters to her sister which she artlessly tells the reader were never intended for publication – included riding alone across the prairie, trying to help a family dying of cholera in the face of indifference from the local inhabitants, a sight of the invalids who were coming to Denver in huge numbers to be cured by the mountain air, and an encounter (if it was nothing more) with that western archetype, the one-eyed, romantic, courteous, poetry-declaiming outlaw, who by the following year was 'in a dishonoured grave, with a rifle bullet in his brain'